Preliminary Evidences of Safety and Efficacy of Flavonoids- and Omega 3-Based Compound for Muscular Dystrophies Treatment: A Randomized Double-Blind Placebo Controlled Pilot Clinical Trial - Sitzia, Clementina; Meregalli, Mirella; Belicchi, Marzia; Farini, Andrea; Arosio, Maddalena; Bestetti, Denise; Villa, Chiara; Valenti, Luca; Brambilla, Paolo; Torrente, Yvan (Frontiers in Neurology, 2019)
Background: nutritional compounds can exert both anti-inflammatory and anti-oxidant effects. Since these events exacerbate the pathophysiology of muscular dystrophies, we investigated nutraceutical supplementation as an adjuvant therapy in dystrophic patients, due to low costs and easy route of administration. Moreover, this treatment could represent an alternative treatment for dystrophic patients who do not respond to corticosteroid treatment. Objective: we performed a 24-week follow-up exploratory single centre randomized double-blind placebo controlled study to test the safety and partially the efficacy of daily oral administration of flavonoids- and omega3-based natural supplement (FLAVOMEGA) in patients affected by muscular dystrophy with recognized muscle inflammation. Design: we screened 60 patients diagnosed for Duchenne (DMD), Facioscapulohumeral (FSHD) and Limb Girdle Muscular Dystrophy (LGMD). Using a computer-generated random allocation sequence, we stratified patients in a 2:1:1 ratio (DMD:FSHD:LGMD) to one of two treatment groups: continuous FLAVOMEGA, continuous placebo. Of 29 patients included, only 24 completed the study: 15 were given FLAVOMEGA, 14 placebo. Results: FLAVOMEGA was well tolerated with no reported adverse events. Significant treatment differences in the change from baseline in six-minute walk distance (6MWD; secondary efficacy endpoint) (P=.033) and in isokinetic knee extension (P=.039)(primary efficacy endpoint) were observed in LGMD and FSHD subjects. Serum CK levels (secondary efficacy endpoint) decreased in all FLAVOMEGA treated groups with significant difference in DMD subjects (P=.039). Conclusions: although the small number of patients and the wide range of disease severity among patients reduced statistical significance, we obtained an optimal profile of safety and tolerability for the compound, showing valuable data of efficacy in primary and secondary endpoints.